2021
DOI: 10.1177/0363546521994511
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Demineralized Cortical Bone Combined With Stem Cell–Derived Extracellular Matrix for Regeneration of the Tendon-Bone Interface

Abstract: Background: Poor healing of the tendon-bone interface after rotator cuff repair is one of the main causes of surgical failure. Previous studies demonstrated that demineralized cortical bone (DCB) could improve healing of the enthesis. Purpose: To evaluate the outcomes of hierarchically demineralized cortical bone (hDCB) coated with stem cell–derived extracellular matrix (hDCB-ECM) in the repair of the rotator cuff in a rabbit model. Study Design: Controlled laboratory study. Methods: Tendon-derived stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Researchers have attempted to develop biomaterials using these cell-derived ECM characteristics for the regeneration of various tissues, such as blood vessels, tendons, muscles, bones, and cartilages ( Lu et al, 2011b ; Gu et al, 2014 ; Kim et al, 2015 ; Xing et al, 2017 ; He et al, 2021 ). However, the integumentary system also needs such tissue engineering to treat wide and intractable skin defects such as burns, pressure ulcers, and diabetic ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have attempted to develop biomaterials using these cell-derived ECM characteristics for the regeneration of various tissues, such as blood vessels, tendons, muscles, bones, and cartilages ( Lu et al, 2011b ; Gu et al, 2014 ; Kim et al, 2015 ; Xing et al, 2017 ; He et al, 2021 ). However, the integumentary system also needs such tissue engineering to treat wide and intractable skin defects such as burns, pressure ulcers, and diabetic ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biological grafts based on tissue engineering strategies have offered a novel alternative approach for the treatment of RCT injury. 3 Graft materials—including synthetic materials and extracellular matrix scaffolds, such as acellular dermal matrix, 18 small intestinal submucosa, 6 demineralized bone matrix, 15,31 and ovine forestomach matrix 28 —have been used to repair RCT tears to improve the rate and quality of biological healing.…”
mentioning
confidence: 99%
“…The significant genes are listed in Table 2 and Fig. 3 E. We found that the expression of mineralization markers such as BGN, COL11A1 , and COL10A1 were significantly increased [ [30] , [31] , [32] , [33] ]. Similarly, the expression of vascular and neurological differentiation markers such as COL8A2 and ANKRD1 also increased to a certain extent [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, other studies have shown that the Wnt/β-catenin signaling pathway can promote the odontogenic differentiation of the hDPSCs. The importance of β-catenin has been revealed in several studies [ [30] , [31] , [32] ]. β-catenin is strongly expressed in odontoblasts and is necessary for root formation [ 26 , [27] , [44] ].…”
Section: Discussionmentioning
confidence: 99%